Post-Cataract Surgery Endophthalmitis in a Patient with Type II Diabetes Mellitus: A Case Report - Dedeh Kurniasih; Nur Husnina Desi (JURNAL IMPLEMENTA HUSADA, 2025)
Endophthalmitis is a severe ocular infection that can lead to significant visual impairment if not promptly managed. We report a case of a 56-year-old female with Type II diabetes mellitus who developed endophthalmitis in the right eye on the 10th day after an uncomplicated cataract surgery. Initially, the patient had good visual recovery (6/6), but she experienced sudden ocular pain and blurred vision with visual acuity declining to 1/300. The diagnosis of endophthalmitis was confirmed, and prompt intravitreal antibiotic therapy was initiated. Following eight days of treatment, her symptoms were resolved, and her vision improved to pre-surgical levels. This case highlights the importance of early recognition and treatment of post-cataract surgery endophthalmitis, especially in diabetic patients who may be at higher risk.